POLA KOMUNIKASI INTERPERSONAL ANAK AUTIS DI SEKOLAH AUTIS FAJAR NUGRAHA YOGYAKARTA - Maria Anggita Karningtyas; Ida Wiendijarti; Agung Prabowo (Jurnal Ilmu Komunikasi, 2009)
This research is motivated by the idea that humans are social creatures or people who can not live alone and will always be in touch with others in the surrounding environment. Humans can interact with one another to communicate with one another, or maybe by giving signs that can be understood by normal humans. However, is not the case with some people who have special needs, including in children with autism, because children with autism just busy with himself. Based on this background, the formulation of problems that researchers took is’’how interpersonal communication patterns children with autism in social interactions with the environment?’’ The method used in analyzing patterns of interpersonal communication in autistic children’s social interaction with the environment in the Autism School Fajar Nugraha Yogyakarta is a descriptive exploratory qualitative method, in which researchers tried to dig deeper when doing research. Based on these results, can be explained that the pattern of interpersonal communication in autistic children communicate and interact with the environment is way wrong if there is not the first approach to the child if the child is not a good mood, and if there is no eye contact with the children. Communication patterns can occur in both directions if there is al- ready the first approach to the child if the child is a good mood, and if there is eye contact with children. Communication process is always spontaneous, because autistic children can not concentrate for long periods of time. The children with autism to communicate with verbal and non verbal language. Non-verbal language such as screams, eye hand movements, and gestures. Children with autism are more likely to use non-verbal language of children with autism because they are children who have the disorder and difficulty in communicating orally.